CCL23 suppresses liver cancer progression through the CCR1/AKT/ESR1 feedback loop. Issue 8 (19th June 2021) - Meng, Jin; Wang, Lianghai; Hou, Jun; Yang, Xiaofeng; Lin, Ke; Nan, Hongxing; Li, Man; Wu, Xiangwei; Chen, Xueling
Abstract: With the ability to activate certain signaling pathways, chemokines and their receptors may facilitate tumor progression at key steps, including proliferation, immunomodulation, and metastasis. Nevertheless, their prognostic value and regulatory mechanism warrant thorough studies in liver cancer. Here, by screening the expression profiles of all known chemokines in independent liver cancer cohorts, we found that CCL23 was frequently downregulated at mRNA and protein levels in liver cancer. Decreased CCL23 correlated with shortened patient survival, enrichment of signatures related to cancer stem cell property, and metastatic potential. In addition to serving as a tumor suppressor through recruiting CD8 + T cell infiltration in liver cancer, CCL23 could repress cancer cell proliferation, stemness, and mobility. Mechanistically, the expression of CCL23 was transcriptionally regulated by ESR1. On the other hand, CCL23 could suppress the activation of AKT signaling and thus promote the expression of ESR1, forming a feedback loop in liver cancer cells. Collectively, these findings reveal that loss of CCL23 drives liver cancer progression by coordinating immune evasion and metastasis initiation. Targeting the ESR1/CCL23/CCR1/AKT regulatory axis could be an effective therapeutic strategy. Abstract : Downregulated expression of CCL23 is associated with poor prognosis in liver cancer. Loss of CCL23 drives liver cancer progression by coordinating immune evasion and metastasis initiation. Mechanistic study reveals an ESR1/CCL23/CCR1/AKT feedback loop.